2017
DOI: 10.1093/cercor/bhx223
|View full text |Cite
|
Sign up to set email alerts
|

Development of Right-hemispheric Dominance of Inferior Parietal Lobule in Proprioceptive Illusion Task

Abstract: Functional lateralization can be an indicator of brain maturation. We have consistently shown that, in the adult brain, proprioceptive processing of muscle spindle afferents generating illusory movement of the right hand activates inferior frontoparietal cortical regions in a right-side dominant manner in addition to the cerebrocerebellar motor network. Here we provide novel evidence regarding the development of the right-dominant use of the inferior frontoparietal cortical regions in humans using this task. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 77 publications
11
42
1
Order By: Relevance
“…This developmental period appears to correspond well with the suppression of executive function timing implemented in the ipsilateral M1 by the development of inhibitory systems, such as transcallosal inhibition from the contralateral M1 (Hanakawa et al , ). If the ipsilateral SM1 deactivation is associated with the development of interhemispheric inhibition during the childhood‐to‐adolescence transition, this result is compatible with our previous result showing the emergence of right‐hemispheric dominance in bodily recognition during adolescence by suppressing the activity in the left hemisphere (Naito et al , ). The transition to adolescence appears to be a developmental period when lateralized use of cerebral hemispheres is facilitated for some brain functions (at least for bodily recognition and unimanual movements).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This developmental period appears to correspond well with the suppression of executive function timing implemented in the ipsilateral M1 by the development of inhibitory systems, such as transcallosal inhibition from the contralateral M1 (Hanakawa et al , ). If the ipsilateral SM1 deactivation is associated with the development of interhemispheric inhibition during the childhood‐to‐adolescence transition, this result is compatible with our previous result showing the emergence of right‐hemispheric dominance in bodily recognition during adolescence by suppressing the activity in the left hemisphere (Naito et al , ). The transition to adolescence appears to be a developmental period when lateralized use of cerebral hemispheres is facilitated for some brain functions (at least for bodily recognition and unimanual movements).…”
Section: Discussionsupporting
confidence: 92%
“…We then calculated the mean parameter estimate across the participants in each group. Such visualization ensured the validity of our findings in the between‐group comparisons (see also Naito et al , ). Hence, we did not perform any statistical evaluations of the parameter estimation data, thus avoiding the circular evaluation issue raised by Kriegeskorte et al ().…”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…Moreover, it has been demonstrated that 6- to 13-year-old children and adolescents already exhibit activation in the cerebrocerebellar sensorimotor network between the contralateral SM1 and the ipsilateral cerebellar hemisphere (lobules V and VI) when they performed finger-tapping tasks with their right hands, with some quantitative difference from adults (De Guio et al 2012 ; Turesky et al 2018 ). Furthermore, we previously demonstrated that 8- to 11-year-old children recruit the cerebrocerebellar sensorimotor network during kinesthetic (muscle spindle afferent) processing of the right hand (Naito et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%